Preventive Healthcare System and Religious Rites of Burial During Pandemic: A Comparison between Jewish and Islamic Rituals - Abdul Rahman Hussein Obeid; Adnan Moh'D Abdullah Shalash; Tazul Islam (USIM Press, 2024)
Vol. 19No. 2